2001
DOI: 10.1093/bja/87.3.447
|View full text |Cite
|
Sign up to set email alerts
|

Perianaesthetic risks and outcomes of abdominal surgery for metastatic carcinoid tumours †

Abstract: Patients with metastatic carcinoid tumours often undergo surgical procedures to reduce the tumour burden and associated debilitating symptoms. These procedures and anaesthesia can precipitate a life-threatening carcinoid crisis. To assess perioperative outcomes, we studied retrospectively the medical records of adult patients from 1983 to 1996 who underwent abdominal surgery for metastatic carcinoid tumours. Preoperative risk factors, intraoperative complications and complications occurring in the 30 days afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
2
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(66 citation statements)
references
References 27 publications
1
62
2
1
Order By: Relevance
“…Acute intravenous administration of octreotide has been reported to provide rapid reversal of carcinoid crisis, and current focus of carcinoid crisis therapy is to prevent mediator release with octreotide prophylaxis [1, 2, 6, 7, 14,18,19,20]. This has largely replaced use of other drugs for acute treatment.…”
Section: Small Intestinal Net: Pre- and Perioperative Therapymentioning
confidence: 99%
“…Acute intravenous administration of octreotide has been reported to provide rapid reversal of carcinoid crisis, and current focus of carcinoid crisis therapy is to prevent mediator release with octreotide prophylaxis [1, 2, 6, 7, 14,18,19,20]. This has largely replaced use of other drugs for acute treatment.…”
Section: Small Intestinal Net: Pre- and Perioperative Therapymentioning
confidence: 99%
“…For example Kinney et al [10] performed a retrospectively study in a group of patients who were submitted to abdominal surgery for metastatic carcinoid tumors. They found an incidence of intraoperative complication of 11% among patients who did not receive intraoperative octreotide and of 0% among those who received at least one dose.…”
Section: Discussionmentioning
confidence: 99%
“…Massimino et al found octreotide LAR and bolus octreotide were insufficient for preventing intraoperative carcinoid crisis in carcinoid patients while Kinney et al reported differently. (Kinney et al, 2001;Massimino et al, 2013) The overall pooled risk showed perioperative carcinoid crisis was similar despite the prophylactic administration of SSTA (OR 0.44, 95% CI: 0.14 to 1.35, p=0.15) (Figure 2). …”
Section: Meta-analysis For the Prophylactic Efficacy Of Ssta For Carcmentioning
confidence: 99%